Above the Line : Take One - Book 1 - Kingsbury, Karen (Grand Rapids, MI Zondervan, 2009)
Two unknown producers struggle to fulfill their dreams to change lives through the power of film. With millions of investors' dollars on the line, everything starts to fall apart and they realize they may be in over their heads. Is it possible to beat the odds and make a movie unlike anything ever done before? Or, will they lose everything in the process?
Accelerated Reader AR
Keywords: Motion picture producers and directors -- Fiction; Fiction